Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
4x + 4x+2 = 272
<=> 4x + 4x.42 = 272
<=> 4x ( 1 + 42 ) = 272
<=> 4x = 16
<=> x = 2
x3 + x + 2
\(=x^3+x^2-x^2-x+2x+2\)
\(=x^2\left(x+1\right)-x\left(x+1\right)+2\left(x+1\right)\)
\(\left(x+1\right)\left(x^2-x+2\right)\)
c) x3 + 32x - 4
\(=x^3-x^2+4x^2-4x+4x-4\)
\(=x^2\left(x-1\right)+4x\left(x-1\right)+4\left(x-1\right)\)
\(=\left(x-1\right)\left(x^2+4x+4\right)\)
\(=\left(x-1\right)\left(x+2^2\right)\)
d)x3y3 + x2y2 + 4
\(=x^3y^3-4xy+x^2y^2-4xy+4\)
\(=xy\left(x^2y^2-4\right)+\left(xy+2\right)^2\)
\(=xy\left(xy-2\right)\left(xy+2\right)+\left(xy+2\right)^2\)
\(=\left(xy+2\right)\left(xy\left(xy-2\right)+xy+2\right)\)
\(=\left(xy+2\right)\left(x^2y^2-2xy+xy+2\right)\)
\(=\left(xy+2\right)\left(x^2y^2-xy+2\right)\)
e) x3 + 3x2y - 9xy2 + 5y3
\(=x^3-3x^2y+3xy^2-y^3+6x^2y-12xy^2+6y^3\)
\(=\left(x-y\right)^3\left(x^2-2xy+y^2\right)\)
\(=\left(x-y\right)^3\left(x-y\right)^2=\left(x-y\right)^2\left(x-y-1\right)\)
1) \(5^x+5^{x+2}=650\)
\(\Rightarrow5^x.1+5^x.5^2=650\)
\(\Rightarrow5^x.\left(1+5^2\right)=650\)
\(\Rightarrow5^x.26=650\)
\(\Rightarrow5^x=650:26\)
\(\Rightarrow5^x=25\)
\(\Rightarrow5^x=5^2\)
\(\Rightarrow x=2\)
Vậy \(x=2.\)
Mình chỉ làm câu 1) thôi nhé.
Chúc bạn học tốt!
\(PT\Leftrightarrow2^x+2^x.2^4=272\)
\(\Leftrightarrow2^x.17=272\)
\(\Leftrightarrow2^x=16\)
\(\Leftrightarrow x=4\)
2x + 2x+4 = 272
2x + 2x . 24 = 272
2x + 2x . 16 = 272
2x . (16 + 1) = 272
2x . 17 = 272
2x = 16
2x = 24
=> x = 4